Isozyme variation in natural populations of cork-oak (Quercus suber L) - Population structure, diversity, differentiation and gene flow - ElenaRossello, J. A.; Cabrera, E. (SILVAE GENETICA, 1996)
Genetic variation of cork-oak (Quercus suber L.) was investigated in 7 Mediterranean populations in Spain using 13 loci from 7 enzyme systems. Quercus suber was found to possess higher values of heterozygosity (H = 0.288 +/- 0.069), percent of polymorphic loci at the 99% criterion (P = 76.9%) and average number of alleles per locus (A = 2.46), than any other oak species. Interpopulation diversity was about 16.9% of the total diversity. The average estimated of Nm based on 10 loci is 2.57, and shows current or recent gene now among populations. Genetic identities among populations were moderate, ranging from I = 0.829 to I = 0.999, and a cluster analysis revealed no patterns related to geography. Our results revealed that the Q. suber populations studied share a common gene pool. The number of alleles and genotypes and the levels of genetic variability in the study populations, indicate that the Spanish populations are genetically rich. These high levels of genetic variability, coupled with the ecological and economic importance of the species make Q. suber a strong candidate for a gene conservation program.
The following values have no corresponding Zotero field: pub-location: FINKENHOFSTRASSE 21, W-6000 FRANKFURT, GERMANY publisher: SAUERLANDERS VERLAG
Keywords: gene diversity; gene flow; genetic differentiation; genetic identities; isozymes; population structure; Quercus suber

Evidence for hybridization between sympatric holm-oak and cork-oak in Spain based on diagnostic enzyme markers - Elena-Rossello, J. A.; Lumaret, R.; Cabrera, E.; Michaud, H. (Plant Ecology, 1992)
Hybridization has been detected in mixed populations of juvenile cork-oak and holm-oak individuals using three diagnostic enzyme loci coding for esterases, leucine amino peptidases and acid phosphatases respectively. Among the 35 studied individuals, 29, 5 and 1 were identified as holm-oak, cork-oak and hybrid respectively. Such diagnostic markers are likely to be useful to detect and remove hybrids at the juvenile stage in areas where the holm-oak is grown for acorn production and the cork-oak is cultivated for cork. This is necessary since hybrid adults produce neither cork nor acorns of high quality.
Keywords: cork-oak; enzyme markers; holm-oak; Hybridization; Quercus